Problems of Elementary School Level Students in Memorizing the Qur’an - Fitriani, Fitriani; Ananda, Muhammad Risky; Saputra, Edriagus; Zahrawani, Sintya Nur; Usmi, Fahrul (International Journal of Multidisciplinary Research of Higher Education, 2022)
This study aims to analyze the problems of elementary school-level students in memorizing the Qur’an. This research uses a qualitative method with a case study approach, research data was taken through direct interviews with ten informants (principals, teachers, and students). All results of interviews and observations were then analyzed thematically with Miles and Huberman’s qualitative data analysis. Overall the results of the analysis showed that there were five problems of elementary school level students in memorizing the Qur’an including: i) lack of time to memorize, ii) lack of ability to read the Qur’an, iii) boredom in memorizing the Qur’an, iv) lack of encouragement from parents in memorizing the Qur’an, v) the influence of online games. The results of this study can be used as initial data for future researchers in examining different issues related to this problem and various other issues relevant to this context.